Knowledge and practices of oil palm smallholders in East Coast Malaysia toward basal stem rot disease (ganoderma boninense) of oil palm - Izzaty Iqlima Norazman; Mohammad Amizi Ayob; Assis Kamu (Kuala Lumpur International Agriculture, Forestry & Plantation Conference, 2016)
Basal stem rot disease (Ganoderma boninense) has been a disruptive disease in oil palm industry of Malaysia and it was first detected in the year 1931. This disease had caused a massive economic losses to the country, reported that annual loss is between RM225 million to RM1.5 billion (Arif et al., 2011). In oil palm industry, oil palm smallholders sector play an important role being part of the supply chain, is positioned at the upstream level, responsible for producing quality fresh fruit bunches (FFB) for the mills as a way of helping the economic development (Rahman and Shariff, 2008). However, smallholders also facing some problems to control the disease spread as such lack of information, inaccessibility and financial constraint in practicing the right agriculture practice in the oil palm cultivation. This paper is to identify and determine the knowledge and practices of oil palm smallholders towards basal stem rot disease (Ganoderma boninense) and also the socio-economic status that influenced their knowledge and practices in oil palm industry. Face to face interview was conducted using a structured questionnaire with a total of 84 respondents among the oil palm smallholders in east coast area of Malaysia. The results indicated that the knowledge of oil palm smallholders towards basal stem rot disease (Ganoderma boninense) is still low and having a good knowledge about a particular subject does not necessarily lead to practice. The relevant parties should involve directly in solving this problem especially in improving the awareness of oil palm smallholders towards the disease.